Association between high oxidized high-density lipoprotein levels and increased pericoronary inflammation determined by coronary computed tomography angiography. Issue 5 (November 2022) - Ichikawa, Keishi; Miyoshi, Toru; Kotani, Kazuhiko; Osawa, Kazuhiro; Nakashima, Mitsutaka; Nishihara, Takahiro; Ito, Hiroshi
Abstract: Background: Impaired high-density lipoprotein (HDL) function is a risk factor for cardiac mortality. We aimed to investigate the association between oxidized HDL (oxHDL) and pericoronary adipose tissue (PCAT) attenuation, a novel imaging biomarker of pericoronary inflammation, by using coronary computed tomography angiography (CTA). Methods: A total of 287 outpatients with suspected coronary artery disease who had undergone both oxHDL measurement and coronary CTA were examined. PCAT attenuation values were assessed at the proximal 10–50 mm segments of the right coronary artery on coronary CTA. The presence of significant stenosis (luminal narrowing of >50 %) and high-risk plaque characteristics were also evaluated. Patients were then classified into tertiles according to their oxHDL level: low (n = 95), moderate (n = 96), and high (n = 96) groups. Results: PCAT attenuation in the high oxHDL group was significantly higher than that in other groups after adjusting for age and apolipoprotein-A-I. Multivariate linear regression analysis revealed that oxHDL was significantly associated with PCAT attenuation in the right coronary artery (β = 3.832, p   <  0.001), whereas HDL cholesterol was not. Furthermore, subgroup analyses demonstrated that the association between oxHDL and PCAT attenuation remained significant in older patients (β = 6.367, p   <  0.001) and in those with hypertension (β = 4.922, p   <  0.011), dyslipidemia (β = 3.264, p   =  0.010), diabetes mellitus (β = 4.284, p   =  0.015), and significant stenosis (β = 3.075, p   =  0.021). Conclusions: High oxHDL levels were significantly associated with increased pericoronary inflammation, as assessed using coronary CTA. Our results may explain the association between impaired HDL function and the development of coronary atherosclerosis. Graphical abstract: Unlabelled Image Highlights: Pericoronary adipose tissue attenuation is a biomarker of pericoronary inflammation. High oxidized high-density lipoprotein levels were associated with high pericoronary adipose tissue attenuation. Impaired high-density lipoprotein function may be involved in pericoronary inflammation.